Upaya Peningkatan Kinerja Tenaga Kependidikan melalui Pelatihan dan Pengembangan di SMA Negeri 13 Surabaya - Falfa Dwika Webiatama, Falfa; Afrizal Nurdin, Muhammad Surya; Windasari, Windasari; Hanivia Cindy, Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Improving the performance of educational staff is an important and relevant challenge in modern education. In the era of globalization and increasingly fierce competition, the skills and knowledge of educational staff are the key to achieving better educational goals. Training and development is an effective way to improve the performance of educational staff. This research examines how training and development at SMAN 13 Surabaya can improve the professionalism and performance of education staff. Through a participatory inductive model approach, this research identifies what factors are the main reasons why SMAN 13 Surabaya carries out training and development in improving the performance of education staff. The results of research at SMAN 13 Surabaya show that training and development that is structured and focused on specific needs can improve the skills, knowledge and professional attitudes of education staff. Apart from that, developing soft skill competencies and critical thinking skills is also important to improve the performance of education staff. This research suggests that integrated and sustainable training and development is the key to achieving significant improvements in the performance of education personnel.